The Influence of Hypnoteaching Method on Students’ Reading Motivation and Achievement in Secondary School - Lismalinda, Lismalinda; Moriyanti, Moriyanti (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
This pre-experimental research was aimed to examine the influence of hypnoteaching method toward students’ reading motivation and achievement. The sample was 40 students with purposive sampling technique. Motivation for Reading Questionnaire (MRQ) and test were the research instruments to gain the data quantitatively. Motivation for Reading Questionnaire (MRQ) adopted from Wigfield and Guthrie (1997) to examine students’ reading motivation levels. For reading achievement, pre-test and post-test were distributed to assess the students’ reading outcome about Narrative Text before and after applying hypnoteaching method. The results of this research showed that the implementation of hypnoteaching method affected students reading motivation and learning outcome. The mean score of pre motivation for reading Questionnaire (MRQ) was 40.2 indicated poor reader and it raised to be 81.1 showing good reader after the implementation of hypnoteaching method. Furthermore, hypnoteaching method also affects English reading result which the mean of pre-test was 45.30 indicating poor score criterion of English subject, meanwhile, after being taught applying hypnoteaching method, the score inclined to 90.25 which asserted good score criterion of English subject. The value of t test was 14.88 from data of pre-test and post-test, however the value of t table was 1.99. It represented that the alternative hypothesis (H1) was accepted and revealed that hypnoteaching method can influence students’ reading achievement. Finally, it was suggested that English teacher should implement this method in teaching English for secondary school students and can be conducted for further research.